(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Ultrasonography plays a crucial role in the assessment of reproductive health and the diagnosis of various gynecological diseases in women. This study aims to evaluate the role and clinical effectiveness of ultrasound in gynecological diagnostics. Many gynecological disorders, such as polycystic ovary syndrome (PCOS), fibroids, and endometriosis, often remain undiagnosed in their early stages, complicating treatment and leading to further health complications. The study utilized a retrospective analysis of clinical data to examine the diagnostic outcomes of ultrasound examinations in gynecological practice. The findings demonstrated that ultrasound is an effective diagnostic tool for identifying structural changes in reproductive organs, including the early detection of PCOS, fibroids, and endometriosis. This early diagnosis is essential for timely treatment and preventing potential complications. Moreover, the results indicate that ultrasonography helps optimize treatment plans by enabling earlier intervention. The study supports the widespread use of ultrasound in gynecology, as it significantly enhances diagnostic accuracy and treatment outcomes. The findings suggest that further development and integration of ultrasound technology can greatly improve reproductive health management and patient care in gynecology.